Surgical revascularization of chronic coronary total occlusions – A systematic review and meta-analysis - Ana Luísa Silva; Gonçalo Ferraz Costa; José Luís Martins; Luís Leite; Lino Gonçalves (Revista Portuguesa de Cardiologia)
Introduction and objectives: Chronic coronary total occlusion (CTO) optimal therapeutic management remains a topic of debate despite its association with adverse clinical outcomes. This study aimed to compare clinical outcomes of patients with CTOs treated with coronary artery bypass graft (CABG) versus medical therapy (MT), assessing the effect of CTO revascularization in patients with multivessel disease undergoing CABG. Methods: In July 2023, PubMed, Embase, Cochrane, and Web of Science databases were systematically searched for studies comparing CTOs treated with CABG versus MT. A sub-analysis of CABG patients, comparing complete surgical revascularization, including CTO bypass, to CABG without CTO bypass, was performed. A pooled odds ratio meta-analysis assessed four main outcomes: mortality, myocardial infarction (MI), stroke, and major adverse cardiovascular events (MACE). The primary outcome was all-cause mortality. Results: Ten observational studies (6458 patients) comparing CABG-CTO with MT-CTO showed lower all-cause mortality in the CABG group (OR 0.31, 95% CI 0.24–0.40, p<0.001, I2=36%). Despite heterogeneity, CABG exhibited reduced CV mortality and MACE (OR 0.37, 95% CI 0.24–0.57, p<0.001, I2=59%; OR 0.37, 95% CI 0.15–0.92, p=0.03, I2=80%, respectively). The MI rate was lower in the CABG group (OR 0.41, 95% CI 0.30–0.56, p<0.001, I2=0%). Comparing bypassed to non-bypassed CTO groups (5 studies, 1949 patients), the bypassed-CTO group had considerably lower MACE (OR 0.49, 95% CI 0.30–0.81, p=0.005, I2=44%). Conclusion: This study suggests a clinical benefit of bypassing a CTO in multivessel disease patients during CABG, with significantly lower MACE. The improved outcomes of CABG over MT further underscore these findings, warranting careful consideration by the Heart Team during their decision-making process. Resumo: Introdução e objetivos: A terapêutica ideal para as oclusões coronárias crónicas (CTO) continua a ser um tópico controverso, apesar de sua associação com eventos clínicos adversos. Este estudo tem como objetivo comparar os doentes submetidos à revascularização cirúrgica da CTO com aqueles tratados com terapêutica médica (TM), avaliando o impacto da revascularização das CTOs em pacientes com doença multivaso submetidos a cirurgia de revascularização miocárdica (CABG). Métodos: Em julho de 2023, estudos a comparar CTOs revascularizadas cirurgicamente com terapêutica médica foram sistematicamente pesquisados nas bases de dados PubMed, Embase, Cochrane e Web of Science. Foi realizada uma subanálise de doentes submetidos a CABG, comparando a revascularização completa, que inclui a revascularização da CTO, com CABG em que a CTO não foi revascularizada. Uma meta-análise agrupada de odds ratio avaliou quatro outcomes principais: mortalidade, enfarte agudo do miocárdio (EAM), acidente vascular cerebral e eventos cardiovasculares adversos major (MACE). Resultados: Dez estudos observacionais (6,458 doentes) que compararam CABG-CTO com TM-CTO mostraram redução da mortalidade global no grupo CABG (OR 0.31, 95% CI 0.24-0.40, p<0.001, I2= 36%). Apesar da heterogeneidade, o grupo CABG-CTO apresentou redução da mortalidade cardiovascular e do MACE (OR 0.37, 95% CI 0.24-0.57, p<0.001, I2= 59%; OR 0.37, 95% CI 0.15-0.92, p = 0.03, I2= 80%, respetivamente). A incidência de EAM foi inferior no grupo CABG (OR 0.41, 0.30-0.56, p<0.001, I2= 0%). Comparando o grupo submetido a bypass da CTO com o não submetido (5 estudos, 1.949 doentes), o grupo com bypass na CTO apresentou redução significativa do MACE (OR 0.49, IC 95% 0.30-0.81, p = 0.005, I2= 44%). Conclusão: Este estudo sugere um benefício clínico da revascularização da CTO em doentes com doença multivaso submetidos a CABG, com redução significativa do MACE. A melhoria dos resultados obtidos com a CABG em comparação com a TM reforça os achados supracitados, destacando a importância de uma avaliação cuidadosa pela Heart Team durante o processo de decisão.